Inhibition of Na/K-ATPase signaling Attenuates Steatohepatitis and Atherosclerosis in Mice Fed a Western Diet: pNaKtide Attenuates Steatohepatitis and Atherosclerosis - Sodhi, Komal; Srikanthan, Krithika; Goguet-Rubio, Perrine; Nichols, Alexandra; Nawab, Athar; Shah, Preeya; Chaudhry, Muhammad; El-Hamdani, Mehiar; Xie, Zijian; Shapiro, Joseph (Cellular and Molecular Biology, 2023)
We have previously reported that the α1 subunit of sodium-potassium adenosine triphosphatase (Na/K-ATPase), acts as a receptor and an amplifier for reactive oxygen species, in addition to its distinct pumping function. On this background, we speculated that the blockade of Na/K-ATPase-induced ROS amplification with a specific peptide, pNaKtide, might attenuate the development of steatohepatitis. To test this hypothesis, pNaKtide was administered to a murine model of NASH: the C57Bl6 mouse fed a “western” diet containing high amounts of fat and fructose. The administration of pNaKtide reduced obesity as well as hepatic steatosis, inflammation and fibrosis. Of interest, we also noted a marked improvement in mitochondrial fatty acid oxidation, insulin sensitivity, dyslipidemia and aortic streaking in this mouse model. To further elucidate the effects of pNaKtide on atherosclerosis, similar studies were performed in ApoE knockout mice also exposed to the western diet. In these mice, pNaKtide not only improved steatohepatitis, dyslipidemia, and insulin sensitivity but also ameliorated significant aortic atherosclerosis. Collectively, this study demonstrates that the Na/K-ATPase/ROS amplification loop contributes significantly to the development and progression of steatohepatitis and atherosclerosis. Furthermore, this study presents a potential treatment, the pNaKtide, for the metabolic syndrome phenotype.